DAMPAK ALIH FUNGSI LAHAN SAWAH TERHADAP PEMANFAATAN SUMBERDAYA AIR UNTUK MENUNJANG KETAHANAN PANGAN - I Gusti Ngurah Santosa; Gede Menaka Adnyana; I Ketut Kartha Dinata; I Gusti Alit Gunadi (Bumi Lestari Journal of Environment, 2010)
Land and water resources are important roles to keep the sustainability of food production. However, these resources tend to decrease because of developing infrastructure as well building, road, industry, tourism, property, etc. In two decades, it was predicted that land farm alleviation in Indonesia was about 10,000 ha per year. On the other side, food demand tended to increase because of population growth. Consequently, study has to be done to get some information about land area, irrigation facilities, and crops production. The location of the study on one unit area of irrigation, named Daerah Irigasi (DI) Mambal. This study was conducted by survey and field experiment on rice package technology. Survey method was done by interview and literature study. The field experiment was done by some modified input i.e. younger seedling, minimum dosage of complete fertilizer, and minimum water irrigation. These treatments were compared to farmer’s technology, and the result was analyzed by t test. The result of the study revealed that the land alleviation was 38.17% (4,280 ha to 2,980 ha) in a period of 30 years at DI Mambal and the land alleviation at Subak Sempidi was 26% (135 ha to 99 ha) in a period of 24 years. The supply of irrigation water debit at DI Mambal decreased 15% (from 3,596 l/sec to 3,038 l/sec) in a period of 30 years. On the other hand, the supply of irrigation water debit at Subak Sempidi increased 26% (from 168 l/sec to 212 l/sec) from 2005 to 2008. As a final point, supply of irrigation water debit increased from 1.70 l/sec/ha on 2005 – 2007 to 2.14 l/sec/ha on 2008. Paddy yield on experiment of technology package was 12.39 ton of dry grain harvest and it was 11.47 ton of dry grain harvest by the farmer’s technology. From the result of the study was suggested that technology package have to be done by two or three times of cultivation to identify the stability of each harvest yield.